1994
DOI: 10.1063/1.467327
|View full text |Cite
|
Sign up to set email alerts
|

The effect of apolar solutes on water structure: Alcohols and tetraalkylammonium ions

Abstract: Neutron diffraction with hydrogen/deuterium isotope substitution on the solvent water hydrogens is used to investigate changes in water structure around the apolar groups on alcohols and tetraalkylammonium ions at room temperature. The HH and HX correlations (where X is a nonsubstituted atom) are calculated for the following solutes in water: ethanol (5 mol%), tertiary butanol (3 mol%), tetrapropylammonium bromide (2.4 mol%), and tetrabutylammonium bromide (1.7 mol%). The correlation functions suggest that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
114
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(133 citation statements)
references
References 27 publications
18
114
0
1
Order By: Relevance
“…For instance, in neutron scattering studies the oxygenoxygen distances of the solvating water molecules were observed to be similar as in bulk liquid water. [2][3][4][5] However, the dynamics of water molecules surrounding hydrophobic groups were observed to be very different from bulk liquid water. In both NMR and femtosecond midinfrared spectroscopy measurements, it was observed that the solvating water molecules show much slower orientational dynamics than the molecules in bulk liquid water.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in neutron scattering studies the oxygenoxygen distances of the solvating water molecules were observed to be similar as in bulk liquid water. [2][3][4][5] However, the dynamics of water molecules surrounding hydrophobic groups were observed to be very different from bulk liquid water. In both NMR and femtosecond midinfrared spectroscopy measurements, it was observed that the solvating water molecules show much slower orientational dynamics than the molecules in bulk liquid water.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested [1,3,4,5,7,10,16,17] that hydrophobic solutes enforces the network of hydrogen bonded water molecules around it and decreases their mobility, a notion referred to as hydrophobic hydration [34,35]. However, recent experimental and computational studies have shown that for small alcohols the structure and dynamics of the water molecules in the solvation shell is almost identical to that of bulk water [23,24,31].…”
Section: Introductionmentioning
confidence: 99%
“…Mixtures of water and ethanol have been studied extensively, both experimentally as by molecular simulation. Experimental studies employing NMR [13,14,15,16,17], ultrasonic absorption [18], infrared absorption spectroscopy [14,15,19,20], mass spectroscopy [19,21], X-ray diffraction measurements [19,22], neutron diffraction [22,23,24], and dielectric relaxation measurements [25,26,27,28] have been performed to unravel the solvation properties of ethanol. Molecular simulation studies using empirical force fields have addressed the equation of state, thermodynamics, and structure and dynamics of solvation [29,30,31,32,33] of aqueous ethanol solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the small population of molecules in this sub-region is compatible with the fact obtained from neutron diffraction experiments for aqueous solutions containing small hydrophobic solutes. 15,16 Neutron diffraction measurements do not show a particular enhancement in the disordered tetrahedral network of pure water. The small fraction of first-shell water molecules really affected by the non-polar solute has a marginal effect on the experimental diffractograms, which are dominated by bulk water molecules.…”
Section: A Orientational Distributionmentioning
confidence: 99%
“…On the iceberg model, Kauzmann 8 proposed the entropic origin of the hydrophobic attraction among caged hydrophobes in water, widely used to explain biochemical processes mediated by water. [12][13][14] During the last two decades, many studies have attempted to confirm experimentally this model by means of different techniques such as neutron diffraction, dielectric relaxation, a) sanchez@us.es and nuclear magnetic resonance, [15][16][17][18][19][20][21][22][23] without reaching a clear evidence for the primitive model. 12,24 The hydrophobicity has also been studied theoretically.…”
Section: Introductionmentioning
confidence: 99%